Localization of geological objects according to magnetometric data with application of algorithms of automated selection - E.P. Lapina; T.L. Miheeva; N.V. Panchenko (Геофизический журнал, 2016)
The method of carrying out quality and quantitative interpretation of basic magnetometric data on the basis of use of analytical approximation of potential fields and some set of derivative highest degrees is offered. In the course of the researches the following tasks are solved: creation of numerical model of the anomalous field is executed, transformant of magnetic field are calculated and quality interpretation of the received results is carried out, modeling local the anamalous of sources is executed. The developed software is tested on the model examples and magnetometric data obtained for the region of the Alushta and Batumi anomalous area in the water area of the Black Sea